A case of endosalpingiosis in submucosa of the urinary bladder - Mishima, Takao (Hinyokika kiyo. Acta urologica Japonica, 2013)
A 39-year-old woman showed thickening of the bladder wall on magnetic resonance imaging (MRI). Since transurethral resection to the lesion revealed that the histological structure of the lesion was compatible with that of the fallopian tube and endometrium, we considered that the tumor was derived from müllerian tissue. Subsequently, partial cystectomy was performed to remove the tumor. Immunohistochemical examination indicated a diagnosis of endosalpingiosis involving endometriosis. The concept of endosalpingiosis was proposed in 1930, and only 9 cases of urinary bladder endosalpingiosis have been reported worldwide. Surgical procedures such as transurethral resection and partial cystectomy were performed in all reported cases. None of the reported cases, including the present case, showed recurrence